Kinetic Monte Carlo simulations of vacancy evolution in graphene. (February 2016) - Parisi, L.; Di Giugno, R.; Deretzis, I.; Angilella, G.G.N.; La Magna, A.
Abstract: Kinetic lattice Monte Carlo simulations, implementing ab initio calibrated energetics, are applied to study the evolution of vacancy systems in graphene. The evolution of the under-coordinated atomic layer proceeds, in general, by island nucleation and growth. However, the first stage (nucleation) is strongly influenced by the stability of small aggregates (e.g. di-vacancies) and by the effective coalescence/attachment barriers. Quantitative predictions of the system kinetics in terms of crystal state and defects' morphology as a function of the initial state and the temperature can be obtained and readily compared with experimental structural characterization of processed samples.